Analysis of Student Learning Outcomes in Physics Subject of Class - Yusi Junianingsih; Arip Nurahman; Dini Andriani (STKIP Harapan Bima, 2026)
This study aims to analyze student learning outcomes in Physics based on Midterm Test (UTS) completion scores. A descriptive method with a qualitative approach was used, with data collected through survey and documentation techniques from class X-C of SMA Muhammadiyah Banyuresmi, consisting of 24 students (14 male, 10 female). The results show that the average student score was 38.75, with only 4 students (16.7%) achieving completion while 20 students (83.3%) had not completed and required remedial teaching. The average score falls within the 35-54 interval, categorized as low. Frequent mobile phone use during lessons and the dominance of conventional, teacher-centered lecture methods were identified as key contributing factors. These findings indicate the need to evaluate the physics learning process and to design more effective and engaging teaching strategies to improve students' conceptual understanding.